Nucleotide sequence of the leukotoxin genes of Pasteurella haemolytica A1. - Lo, R Y (1987)
A 4.4-kilobase-pair DNA fragment coding for the leukotoxin of Pasteurella haemolytica A1 has been isolated, and its nucleotide sequence has been determined. Two open reading frames, designated lktC and lktA, coding for proteins of 19.8 and 101.9 kilodaltons, respectively, were identified. Expression of the two genes in minicell-labeling experiments resulted in the production of the predicted proteins LKTC and LKTA. By using an antiserum against the soluble antigens of P. haemolytica A1 in Western blot (immunoblot) analysis of total cellular proteins from the Escherichia coli clones, LKTA was identified as an additional antigenic protein. Results from subcloning of the DNA fragment suggested that expression from both lktC and lktA is required for leukotoxin activity, indicating that the leukotoxin of P. haemolytica A1 is encoded by two genes. A comparison of the organization and the DNA sequence of the leukotoxin genes with those of the E. coli alpha-hemolysin genes showed a significant degree of homology between the two loci. This analysis suggested that the leukotoxin genes of P. haemolytica A1 and the E. coli alpha-hemolysin genes may have evolved from a common ancestor and that the two toxins may share similar activities or functional domains or both.